1986
DOI: 10.1042/bj2350103
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-associated pyruvate kinase in developing guinea-pig liver

Abstract: During analysis of pyruvate kinase distribution in developing guinea-pig liver it was observed that a substantial proportion of the activity remained associated with the microsomal membrane fraction ('microsomes'). Although some of this could be removed by washing with sucrose, the majority required detergent treatment for liberation, and even then at least one-half remained attached to the microsomes. Estimates of the contribution of this fraction to total cell pyruvate kinase activity indicated that it was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Glycolytic enzymes, long identified as soluble proteins of the cytoplasm, have been found to be ambiquitous (defined as having the ability to be distributed either on a structure or dispersed within a solution) depending on cytosolic conditions [ 17 ]. Many of the glycolytic enzymes have been proposed to bind cellular structures, as evidenced by their presence in insoluble cellular fractions [ 18 , 19 , 20 , 21 , 22 ]. For example, studies in cardiac and skeletal muscle have shown localization of glycolytic enzymes to the ATPase calcium pumps on the sarcoplasmic reticulum [ 23 , 24 ].…”
Section: Behavior Of Glycolytic Enzymesmentioning
confidence: 99%
“…Glycolytic enzymes, long identified as soluble proteins of the cytoplasm, have been found to be ambiquitous (defined as having the ability to be distributed either on a structure or dispersed within a solution) depending on cytosolic conditions [ 17 ]. Many of the glycolytic enzymes have been proposed to bind cellular structures, as evidenced by their presence in insoluble cellular fractions [ 18 , 19 , 20 , 21 , 22 ]. For example, studies in cardiac and skeletal muscle have shown localization of glycolytic enzymes to the ATPase calcium pumps on the sarcoplasmic reticulum [ 23 , 24 ].…”
Section: Behavior Of Glycolytic Enzymesmentioning
confidence: 99%